2021
DOI: 10.1186/s12951-021-00987-1
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins are unevenly distributed across single extracellular vesicles and bias sensitivity to multiplexed cancer biomarkers

Abstract: Background Tetraspanin expression of extracellular vesicles (EVs) is often used as a surrogate for their detection and classification, a practice that typically assumes their consistent expression across EV sources. Results Here we demonstrate that there are distinct patterns in colocalization of tetraspanin expression of EVs enriched from a variety of in vitro and in vivo sources. We report an optimized method for the use of single particle antibo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 58 publications
8
67
0
Order By: Relevance
“…Single-particle flow cytometry, such as image flow cytometry (IFCM), can analyze single sEV subpopulations by their surface protein profile, such as tetraspanins, at a high throughput rate [ 21 , 26 , 27 ]. However, it comes with a theoretical detection limit of around 80 nm for sEV [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single-particle flow cytometry, such as image flow cytometry (IFCM), can analyze single sEV subpopulations by their surface protein profile, such as tetraspanins, at a high throughput rate [ 21 , 26 , 27 ]. However, it comes with a theoretical detection limit of around 80 nm for sEV [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Good consistency exists in the tetraspanin profile of exosomes from the same source regardless of isolation methods. But the results confirmed that tetraspanin profiles of exosomes from a different source are distinct ( 134 ). Additionally, other exosomal cargos can also differ among different sources.…”
Section: Conclusion and Perspectivementioning
confidence: 52%
“…Until antibodies specific to equine EV-related proteins become available, we recommend using a combination of methods, including techniques that do not require antibodies, such as NTA and TEM. TEM can discriminate single EVs from similar-sized non-EV particles and is therefore widely used to monitor the quality and purity of EV-containing samples, e.g., for therapeutic application or downstream analysis [ 53 , 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%